Prevalence of cervical rib in patients visiting department of Radiodiagnosis at a tertiary care hospital: A descriptive cross-sectional study - Pandit, Ruku; Adhikari, Aarati; Sharma, Nitasha; Upadhyay, Hari Prasad (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: The cervical ribs are the supernumerary ribs that are often associated with neuro-vascular symptoms in thoracic outlet syndromes. The objective of the study is to find the prevalence of cervical ribs among the patients visiting the Radiodiagnosis department of a tertiary care hospital. Methods: This is a cross-sectional study comprising 1533 chest and cervical spine radiographs of patients visiting the Radiodiagnosis department of a tertiary care hospital from March to June 2021. Ethical approval was taken from the Institutional Review Committee at the College of Medical Sciences and Teaching Hospital (Reference Number: COMSTH-IRC/2021-63). The presence or absence of a cervical rib was noted in the digital x-rays. The collected data were statistically analyzed using Statistical Package for Social Science version 20. Results: The prevalence of cervical ribs was 1.5%, with males and females accounting for 0.85% and 0.65% respectively. Amongst the cases with cervical ribs, the unilateral (73.91%) cervical rib was significantly more than bilateral (26.01%) occurring more frequently on the left side. The cervical rib was found to be more predominant in males than in females without significant difference. Sexual dimorphism was not found to be significantly associated with laterality and sidedness of cervical ribs. Conclusions: The cervical ribs were commonly encountered in our study. As the presence of the cervical rib is one of the leading causes of thoracic outlet syndromes, clinicians should not overlook the existence of cervical ribs while ruling out the etiology of thoracic outlet syndromes.